Repetitive ozone exposure worsens features of muco-inflammatory disease in developed Scnn1b-Tg+ mice lungs - Vo, Thao; Patial, Sonika; Saini, Yogesh (Frontiers in Toxicology, 2025)
IntroductionAmbient exposure to ozone (O3), one of the six criteria pollutants, is associated with the exacerbation of respiratory symptoms in individuals with underlying lung diseases. Using Scnn1b-Tg+ (Tg+) mice, a widely used model of muco-inflammatory lung disease, we have demonstrated that O3 exposure during the early stages of postnatal lung development leads to exacerbated muco-inflammatory outcomes. However, it remains unclear whether O3 affects the developed lungs differently than the underdeveloped lungs of Tg+ mice.MethodsWe exposed 3-week-old wild-type (WT) and Tg+ mice to either filtered air (FA) or 0.8 ppm O3 for 3 weeks and examined the lung phenotypes 12-16 h post-last exposure.ResultsAs compared to FA-exposed WT mice, O3-exposed WT mice showed increased bronchoalveolar lavage fluid (BALF) proteins, increased immune cells, increased inflammation, alveolar space enlargement, and tissue consolidation. As compared to FA-exposed WT mice, the FA-exposed Tg+ mice showed increased immune cells, elevated levels of inflammatory mediators, e.g., IL-5, G-CSF, MIP-2, KC, MIP-1α, MIP-1β, IP-10, TNF-α, and IL-17, increased inflammation, alveolar space enlargement, tissue consolidation. As compared to FA-exposed Scnn1b-Tg+ mice, O3-exposed Tg+ mice had increased total protein, total dsDNA, and phagocytosed lipid contents, in addition to exaggerated granulocytic recruitment, peripheral and bronchiolar inflammation, alveolar space enlargement, and tissue consolidation.DiscussionTogether, our data using Tg+ mice with developed lungs exhibited several findings consistent with previous findings observed in Tg+ neonates. Interestingly, however, as opposed to the previous report in O3-exposed neonatal Tg+ mice, where the hallmark features of Tg+ airway disease, i.e., mucus obstruction and expression of major gel-forming mucins (MUC5B and MUC5AC) were found exacerbated by O3 exposure, the FA- and O3-exposed Tg+ mice with developed lungs exhibited comparable responses. These differential responses suggest that the stage of lung development is an important factor in the modulation of epithelial remodeling following O3 exposure.